Wirtschaftliche Stagnation als "neue Normalsituation"? Rezension von: Galbraith, James, The End of Normal. The Great Crisis and the Future of Growth, Simon and Schuster, New York 2014, 291 Seiten - Philipp Heimberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2016)
Rezension von Galbraith, James, The End of Normal. The Great Crisis and the Future of Growth, Simon and Schuster, New York 2014, 291 Seiten; ISBN 978-1451644920
Keywords: 330